Trichoderma koningiopsis Tk905: an efficient biocontrol, induced resistance agent against banana Fusarium wilt disease and a potential plant-growth-promoting fungus - Luo, Mei; Chen, Yue; Huang, Qiurong; Huang, Zhenxin; Song, Handa; Dong, Zhangyong (Frontiers in Microbiology, 2023)
Fusarium oxysporum f. sp. cubense tropical race 4 (FocTR4) is a devastating phytopathogen responsible for significant losses in banana production worldwide. Trichoderma and other biocontrol agents (BCAs) have been used as suitable disease control methods for banana Fusarium wilt. In this study, the endophytic T. koningiopsis Tk905 strain was isolated from the roots of dendrobe plants and identified utilizing morphological and molecular analyses. Antifungal activity tests revealed that Tk905 effectively inhibited mycelial growth with inhibition rates ranging from 26.52 to 75.34%. Additionally, Tk905 covered the pathogen mycelia, and spores were observed on or around the pathogen hyphae. The average root and shoot fresh weights and plant height, of Tk905-inoculated plants were significantly higher than those of the untreated plants. Furthermore, Tk905 treatment significantly increased the activity of antioxidant enzymes, such as catalase (CAT), phenylalanine ammonia-lyase (PAL), polyphenol oxidase (PPO), and peroxidase (POD), suggesting that Tk905 may enhance plant defence systems by activating their antioxidant mechanisms. Most importantly, Tk905-treated plants inoculated by three methods exhibited significantly lower disease incidence and severity than untreated plants. The protective effects of Tk905 against FocTR4 infection were not only observed in the early stages of infection but persisted throughout the experiment, suggesting that T. koningiopsis Tk905 can provide long-lasting protection against Fusarium wilt.